High-Pressure Treatment in Combination with Reduced Sodium for Improving the Physicochemical Properties and Sensory Qualities of Pork Gels - Weitong Wang; Jingying Cai; Satomi Tsutsuura; Tadayuki Nishiumi (Foods)
High-pressure treatment was utilized in this study to produce high-quality, reduced-sodium pork gels with desirable texture and sensory properties, addressing the challenge of maintaining quality in low-sodium meat products to meet health-conscious consumer demands. High-pressure treatment applied within the range of 150–200 MPa significantly reduced cooking loss while maintaining moisture content and provided an ideal network structure for reduced-sodium pork gels. High-pressure treatment at up to 100–200 MPa, in combination with added sodium chloride and sodium polyphosphate, was evaluated for its effects on gel texture, with results indicating that high-pressure treatment significantly improved breaking stress (increased by 10.01% under 150 MPa and 14.66% under 200 MPa), modulus of elasticity (increased by 14.77% under 150 MPa and 24.17% under 200 MPa), and hardness (increased by 11.12% under 150 MPa and 11.45% under 200 MPa). Rheological characteristic measurements revealed that gel strength was highest at 150 MPa (G′ = 443,000 Pa; G″ = 66,300 Pa and <semantics>tan<mspace width="0.166667em"></mspace>δ</semantics> = 0.15), which showed higher G′ and G″ values and similar <semantics>tan<mspace width="0.166667em"></mspace>δ</semantics> compared to the 0.1 MPa, 2% NaCl + 0.5% SPP condition (G′ = 334,000 Pa; G″ = 49,200 Pa; <semantics>tan<mspace width="0.166667em"></mspace>δ</semantics> = 0.148). Protein analysis by sodium dodecyl sulfate–polyacrylamide gel electrophoresis showed a reduction in the <semantics>α</semantics>-actinin band with increased pressure, which suggested protein interactions were enhanced. Differential scanning calorimetry analysis indicated that protein denaturation occurred more readily at higher pressures (0.071 J/g at 0.1 MPa, 0.057 J/g at 150 MPa, and 0.039 J/g at 200 MPa). These findings underscore the value of treatment under high pressure at 150 MPa developing reduced-sodium meat products with desirable texture and flavor characteristics.